Development Of The Snake Ladder Math Game On Fraction Material In Class IV - Furqon, Marshanda Afifah; Irawati, Riana; Maulana (Universitas PGRI Yogyakarta, 2024)
Abstract The aim of this research is to determine the feasibility of the Snake Ladder Math Game on fraction material in class IV. This research uses the Research and Development (R&D) method with the aim of determining the feasibility of a product that has been made. The steps used in this research are Analysis, Design, Development, and Evaluation. This research has only reached the product development and validation stage with expert validators and has not yet reached the testing stage. This research uses quantitative data to see the feasibility of the product from expert assessments and also uses qualitative data from suggestions, input, criticism from validators through the questionnaire provided. The data collection technique uses a media and material expert validator assessment questionnaire to determine the feasibility of the Snake Ladder Math Game development product. The results of this research show that the validation percentage results from validator material expert 1 was 84.09% and material expert 2 was 81.81%. The percentage results for media expert 1 were 80.76% and media expert 2 was 88.46%. The average assessment of material experts is 82.95% and the average assessment of media experts is 84.61%, indicating that this category is Very Good. This shows that the Snake Ladder Math Game is suitable for use in learning fraction material in class IV. Keywords: Learning Media, Development, Fractions at